Exploring the Relationship between Interactional Competence and Group Oral Communication - Ezihaslinda, Ngah; Siti Hamin, Stapa (UMP Press, 2019)
From job interviews to working in a professional field, clear and effective interactional competence especially in face-to-face oral communication is vital for workplace interactions. As such, group oral communication is taught and assessed at academic institutions to enhance students’ turn-taking skills as an interactional competence. The approach is used to develop ESL students’ turn-taking skills particularly for low proficiency students. Therefore, this study aims to explore turn-taking skills of low proficiency ESL students in a mixed ability group discussion assessment. The group discussion interactions were audio visually recorded and analysed using Conversation Analysis. The transcriptions were analysed using the micro-analysis account focusing only on the turn-taking skills. Notably, self-selected, or indexical speaker selection by posing questions for another speaker to continue or using gaze or gestural signs was the prominent turn-taking skill used by the students to maintain intersubjectivity during group discussion. This somehow facilitated them in ensuring active involvement of all group members, and as an indicator for their interactional competence. This study concludes by discussing how turn-taking skills in group oral communication can benefit low proficiency language users’ interactional competence in learning the target language.